Factors contributing to the delay of discharge medication in medical ward - Mohd Zahar, Iman Syuhada; Mohamad, Muhamad Illias; Mohamed Zain, Muhamad Zaidi (2016)
Detainment in discharge from acute hospitals is very critical nowadays. Acute care can be defined as having severe symptoms and a short course. Most of hospitals in Malaysia share the same problems in discharging patients especially in medical ward. Little is known on the factors that influence the delay of discharging medication. This study examines which factors that contributes to the delay of discharging medication in ward supply for medical ward. The study period is about a month that was started on December 2015, data on the time for medication to be discharged out from pharmacy was precisely calculated and collected. A set of questionnaire was then distributed to the pharmacist, assistant pharmacist and provisionally registered pharmacist to identify which factors that contribute the most to the delay of discharging medication from ward supply. Based on our study in Hospital Selayang, 89 patients from Medical Ward with medication were discharge within three hours due to no medical problems whereas 20 of them were late to be discharged because of medication problems. This made up 82% and 18% respectively. There were external and internal factors that affect discharge medication in ward supply. The external factors are prescription waiting to be modified, late medication order by the doctor, doctor not contactable, staff nurse does not alert with ‘ready for collection’ discharge medication, ‘Jawatankuasa Therapeutic Ubat’ (JKTU) and ‘Ketua Pengarah Kesihatan’ KPK items that have to key-in in system takes much of time and lack of staff in handling discharge medication. The internal factors are from the ward supply that related to the system of prescribing by the doctor Total Health Information System (THIS), printing system and i-Monitor which is pharmacy service monitoring system.